Current Status of The Postal Service Republic of Uzbekistan - Nazarova Gulchexra Nurmuxanbetovna (Zien Journals, 2021)
This article is about the Postal Service of today's Uzbekistan and the changes in it. The purpose of this article is to provide a more consistent development of the postal network system and to fill it with the necessary personnel
Keywords: Postal communication network; country structurally consists; regional branches